From growth failure to gait failure: Arnold-Chiari 1 malformation in a teenager - Koirala, Satya Prasad; Islam, Md. Rafayel; Banu, Hurjahan; Sultana, Nusrat; Jahan, Sharmin; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Arnold-Chiari 1 malformation is a congenital anomaly of the craniovertebral junction, often presenting with diverse neurological, endocrine, and musculoskeletal manifestations. Growth and pubertal delay may coexist with neurological deficits, making early recognition essential. Here we report a 17-year-old male, 3rd issue of non-consanguineous parents, admitted to BMU with growth failure for 6-8 years and progressive difficulty in walking along with gait abnormality for 4 years. He experienced chronic occipital headaches, blurring of vision, and occasional dizziness. Pubertal delay was evident by underdeveloped secondary sexual characteristics, notably scanty facial hair and an underpitched voice. Examination reveals short stature (H-147 cm, SDS -2.6) and delayed puberty (Tanner-P2, left testis 10 ml, right undescended testis palpable in the inguinal region). Neurological signs included dysarthria, tongue fasciculation with wasting, exaggerated deep tendon reflex, plantar extensor, positive ankle clonus, wide-based gait, and other cerebellar dysfunctions. Biochemically, GH deficiency was found. MRI of the spine showed dysplastic occipital condyle with foramen magnum stenosis, cervico-medullary compression indicating Arnold-Chiari 1 malformation. This case illustrates an unusual presentation of chairi-1 malformation with growth retardation and delayed puberty, emphasizing the importance of a multidisciplinary approach for timely diagnosis and management. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S67]